Circaea Mollis Siebold & Zucc. Prevents Bone Loss in a Mouse Postmenopausal Osteoporosis Model by Promoting of Osteoblast Differentiation (P06-130-19) - Yoo, Gyhye (Curr Dev Nutr, 2019)
OBJECTIVES: Postmenopausal osteoporosis, a condition of low bone density consequent to decreased estrogen levels after menopause in women, is generally treated with hormone replacement therapy. However, long-term hormone use may cause critical side effects including breast cancer. Alternatively, phytoestrogens, which have similar structures to steroid hormones, are reported to cure postmenopausal symptoms with fewer side effects. Here, we investigated the effects of EtOH extract of Circaea mollis Siebold & Zucc. (EECM), a traditional herbal medicine in Asia that exhibits anti-arthritic activities, on postmenopausal osteoporosis. METHODS: In vitro model: MCF7 breast cancer cells and MC3T3-E1 pre-osteoblast cells were utilized to estimate estrogenic and osteogenic activity. Osteoblastic markers were measured by western blot and real-time PCR. In vivo model: Female mature C57BL/6 mice were ovariectomized and oral administrated with 10 mg/kg and 40 mg/kg of EECM respectively. RESULTS: EECM increased alkaline phosphatase activity and osteoblastic markers including osteoprotegerin at day 6 during mouse preosteoblast differentiation. EECM inhibited osteoclast differentiation and bone resorption in an osteoblast-osteoclast primary co-culture system via osteoprotegerin-mediated RANK/RANKL signaling. In ovariectomized mice, EECM prevented bone mineral density decrease and recovered osteoblastic molecules. CONCLUSIONS: EECM enhanced the differentiation of osteoblasts via osteogenic markers and modulated RANK/RANKL signaling via an elevation of OPG from osteoblasts in vitro and in vivo. Therefore, EECM may be effective in preventing bone loss and offers a promising alternative for the nutritional management of postmenopausal osteoporosis. FUNDING SOURCES: This work was supported by the Center Project for the Korea-Mongolia Science and Technology Cooperation (2U06170). SUPPORTING TABLES, IMAGES AND/OR GRAPHS: